G83(P) Health and wellbeing profile of looked afterchildren. (24th May 2017) - Keene, J; Mohiddin, A; Wolfe, I
Abstract : Aims: Looked After Children (LAC) are a vulnerable group. UK numbers have increased 1% annually for the past 7 years and services are thought to be variable. Our aim was to produce a comprehensive profile of LAC's health and wellbeing needs. Methods: Systematic review of published literature 2000–2015 relating to LAC health, following references thereafter and review of relevant national publications on problems facing LAC. Results: Sexual Health: LAC are twice as likely to become pregnant compared with peers[11, 12]. 25% of female care leavers become pregnant or give birth within one year of leaving care[13]. Males are more likely to be teenage fathers; 5%–6%% Vs 0.7% teenagers who have never been in care[14] Youth Offending: Care leavers comprise 35% of the prison population under 21 years and 27% overall[15, 16]. 50% of women and 25% men in Young Offenders Institutes have spent time in care[17]. Substance Misuse: 10% of 16–17 year olds report substance misuse issues, despite this only 50% receive an intervention their problem[18]. Cannabis is the most frequently used substance, tried by 73% of LAC[19]. Education: Conclusion: All examined aspects of LAC's health and wellbeing are worse than the non-LAC population. There is significant need within the LAC population, and services for LAC should reflect the high levels of need.